Rational Design, Synthesis and In Vitro Evaluation of Three New Alkylating Steroidal Esters - Fousteris, M. A.; Koutsourea, A. I.; Lagonikakos, N. P.; Arsenou, E. S.; Spyridonidou, C.; Mourelatos, D.; Nikolaropoulos, S. S. (Medicinal Chemistry, 2006)
Recent studies have indicated that minor functional changes on the steroidal part of complex molecules, comprising of an alkylating moiety and a steroidal congener, lead to compounds with enhanced biological activity. The observed induction of the genotoxic, cytotoxic and antileukemic effects suggest a determinative role of the steroidal congener on the mechanism of action. In order to further elucidate the structural requirements responsible for this, we designed and synthesized a new modified steroid, carrying a 17 β-acetamide substituent and a B lactamic ring, and studied the ability of its esters with three potent nitrogen mustards to induce sister chromatid exchange (SCEs) and to inhibit cell proliferation in normal human lymphocytes in vitro. The role of the steroidal skeleton was clearly stated by the results of the in vitro evaluation of the final compounds, as all three derivatives proved better inducers of SCE (58-102 SCE/cell) and cell division delays (1.18-1.25 PRI) than the simple nitrogen mustards (24-38 SCE/cell and 1.51-1.62 PRI). Obviously, the steroidal module enhances the formation of DNA adducts that cannot be repaired by excision repair enzymes probably through the induction of the interaction of these complex compounds with different base sequences or by disabling the repair mechanisms through the blockage of the enzymes responsible for excision repair. On the other hand, it seems that these compounds also act through a parallel site of action responsible for cell death when their primary binding site becomes saturated, as in higher concentrations two of the derivatives tested showed enhanced cytotoxicity while their ability to induce SCE stabilized.
Keywords: Steroidal esters